1997
DOI: 10.1038/385275a0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of substrate-induced conformational changes in phosphoglycerate kinase activation

Abstract: Phosphoglycerate kinase (PGK), a key enzyme in glycolysis, catalyses the transfer of a phosphoryl-group from 1,3-bisphosphoglycerate to ADP to form 3-phosphoglycerate and ATP. Despite extensive kinetic and structural investigations over more than two decades, the conformation assumed by this enzyme during catalysis remained unknown. Here we present the 2.8 A crystal structure of a ternary complex of PGK from Trypanosoma brucei, the causative agent of sleeping sickness. This structure determination relied on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
230
2
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(244 citation statements)
references
References 27 publications
11
230
2
1
Order By: Relevance
“…As shown by crystallographic studies, the triose substrate binds to a basic patch in the N-terminal domain (9) whereas the nucleotide substrate binds to the C-terminal domain (10). Six three-dimensional structures have been solved by x-ray crystallography: the PGK from horse muscle (11)(12)(13), yeast (14,15), pig muscle (9,16), Bacillus stearothermophilus (10), Trypanosoma brucei (17), and Thermotoga maritima (18). Until recently, the reported structures were in a conformational state incompatible with substrate catalysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by crystallographic studies, the triose substrate binds to a basic patch in the N-terminal domain (9) whereas the nucleotide substrate binds to the C-terminal domain (10). Six three-dimensional structures have been solved by x-ray crystallography: the PGK from horse muscle (11)(12)(13), yeast (14,15), pig muscle (9,16), Bacillus stearothermophilus (10), Trypanosoma brucei (17), and Thermotoga maritima (18). Until recently, the reported structures were in a conformational state incompatible with substrate catalysis.…”
mentioning
confidence: 99%
“…Until recently, the reported structures were in a conformational state incompatible with substrate catalysis. The T. brucei ternary complex has been crystallized in the catalytically competent conformation, however, and has shown that the substrates are close to each other and well aligned for phosphoryl transfer (17). Interestingly, the PGK complete hinge closure occurs only when both substrates are bound and depends on their synergistically induced conformational changes.…”
mentioning
confidence: 99%
“…One substrate, ADP, binds an inner face, whereas the other substrate, 1,3-bisphosphoglycerate, binds the opposing inner face. Bringing the lobes together is thought to be involved in catalysis (8,9). As such, crowding would be predicted to increase the enzyme's activity.…”
mentioning
confidence: 99%
“…In the crystal structure, the ADP and diphosphoglycerate binding sites, each located at an N and C subunit, are separated. It has been suggested that a large-scale conformational change (2) is necessary to bring the two subunits together when the phosphoryl group is catalytically transferred, and a hinge-bending mechanism has been postulated (3), bringing together both substrates at the inner surfaces of the C and N subdomains (4,5).…”
mentioning
confidence: 99%